Cytokine Hemoadsorption as Rescue Therapy for Critically Ill Patients With SARS-CoV-2 Pneumonia With Severe Respiratory Failure and Hypercytokinemia - Ruiz-Rodríguez, Juan Carlos; Chiscano-Camón, Luis; Ruiz-Sanmartin, Adolf; Palmada, Clara; Paola Plata-Menchaca, Erika; Franco-Jarava, Clara; Pérez-Carrasco, Marcos; Hernández-González, Manuel; Ferrer, Ricard (Frontiers in Medicine, 2022)
Introduction: A dysregulated inflammatory response, known as “cytokine storm”, plays an important role in the pathophysiology of coronavirus 2019 disease (COVID-19). Identifying patients with a dysregulated inflammatory response and at high risk for severe respiratory failure, organ dysfunction, and death is clinically relevant, as they could benefit from specific therapies, such as cytokine removal by hemoadsorption. This study aimed to evaluate cytokine hemoadsorption as rescue therapy in critically ill patients with SARS-CoV-2 pneumonia, severe respiratory failure refractory to prone positioning, and hypercytokinemia. Methods: In this single-center, observational and retrospective study, critically ill patients with SARS-CoV-2 pneumonia, severe acute respiratory failure, and hypercytokinemia were analyzed. All patients underwent cytokine hemoadsorption using Cytosorb®. The indication for treatment was acute respiratory failure, inadequate clinical response to the prone position, and hypercytokinemia. Results: Among a total of 343 patients who were admitted to the intensive care unit (ICU) due to SARS-CoV-2 infection between March 3, 2020, to June 22, 2020, six patients received rescue therapy with cytokine hemoadsorption. All patients needed invasive mechanical ventilation and prone positioning. A significant difference was found in the pre-and-post treatment D-dimer [17868 mcg/ml (4196– 45287) vs. 4488 mcg/ml (3166– 17076), p = 0.046], C-reactive protein [12.9 mg/dl (10.6) vs 3.5 mg/dl (2.8), p = 0.028], ferritin [1539 mcg/L (764 – 27414) vs 1197 ng/ml (524-3857), p = 0.04] and interleukin-6 [17367 pg/ml (4539– 22532) vs 2403 pg/ml (917-3724), p = 0.043] levels. No significant differences in the pre-and-post treatment interleukin-10 levels [22.3 pg/ml (19.2 – 191) vs. 5.6 pg/ml (5.2-36.6), p = 0.068] were observed. Improvements in oxygenation [pre-hemoadsorption PaO2/FIO2 ratio 103 (18.4) vs. post-hemoadsorption PaO2/FIO2 ratio 222 (20.9), p = 0.029] and in organ dysfunction [pre-hemoadsorption SOFA score 9 (4.75) vs post-hemoadsorption SOFA score 7.7 (5.4), p = 0.046] were observed. ICU and in-hospital mortality was 33.7%. Conclusions: In this case series, critically ill COVID-19 patients with severe acute respiratory failure refractory to prone positioning and hypercytokinemia who received adjuvant treatment with cytokine hemoadsorption showed a significant reduction in IL-6 plasma levels and other inflammatory biomarkers. Improvements in oxygenation and SOFA score were also observed.